2016
DOI: 10.3390/rs8030173
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Classification of South Patagonian Peat Bog Microforms Reveals Potential Gaps in Up-Scaled CH4 Fluxes by use of Unmanned Aerial System (UAS) and CIR Imagery

Abstract: South Patagonian peat bogs are little studied sources of methane (CH 4 ). Since CH 4 fluxes can vary greatly on a small scale of meters, high-quality maps are needed to accurately quantify CH 4 fluxes from bogs. We used high-resolution color infrared (CIR) images captured by an Unmanned Aerial System (UAS) to investigate potential uncertainties in total ecosystem CH 4 fluxes introduced by the classification of the surface area. An object-based approach was used to classify vegetation both on species and microf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 63 publications
(48 reference statements)
5
55
0
Order By: Relevance
“…The orthomosaics of all dates were manually anchored to the first image, using 50 points for each image and the georeferencing function in ArcGIS 10.3 ® software (root mean square error = 2.6 cm). The multi-resolution segmentation algorithm in eCognition essentials 1.3 ® software was used for segmenting the UAV imagery [30,[98][99][100][101][102]. The algorithm defines spatial differentiated polygonal objects on the basis of spatial and spectral homogeneities in the input image [103].…”
Section: Overhead Data Acquisition and Species Classificationmentioning
confidence: 99%
“…The orthomosaics of all dates were manually anchored to the first image, using 50 points for each image and the georeferencing function in ArcGIS 10.3 ® software (root mean square error = 2.6 cm). The multi-resolution segmentation algorithm in eCognition essentials 1.3 ® software was used for segmenting the UAV imagery [30,[98][99][100][101][102]. The algorithm defines spatial differentiated polygonal objects on the basis of spatial and spectral homogeneities in the input image [103].…”
Section: Overhead Data Acquisition and Species Classificationmentioning
confidence: 99%
“…Due to the spatial pattern of vegetation communities in peatland and its microtopographic elements [2,39], ideally the classification of vegetation microforms (e.g., vascular plant-dominated hummocks, exposed mosses in hollows, trees, etc.) in peatlands would utilize very fine spatial-resolution imagery (<1 m) (e.g., [21,40]). However, since we did not have a fine-scale elevation grid for the whole study area, we derived the relationship between PAI and PRI ( Figure 2) and applied it to the CASI imagery from 23 June 2016.…”
Section: Discussionmentioning
confidence: 99%
“…This index originally belongs to narrowband VI (Broge and Leblanc, 2001). Nevertheless, prior applications of the mTVI in a remote sensing study by the authors (Lehmann et al, 2016) also revealed high potential to distinguish plant species using imagery acquired with a self-modified CIR camera sensor.…”
Section: Remote-sensing Approachesmentioning
confidence: 99%